Assessing fatigue in inflammatory bowel disease: comparison of three fatigue scales. Issue 2 (19th May 2015) - Norton, C.; Czuber‐Dochan, W.; Bassett, P.; Berliner, S.; Bredin, F.; Darvell, M.; Forbes, A.; Gay, M.; Ream, E.; Terry, H.
Summary Background Fatigue is commonly reported by patients with inflammatory bowel disease (IBD), both in quiescent and active disease. Few fatigue scales have been tested in IBD. Aim To assess three fatigue assessment scales in IBD and to determine correlates of fatigue. Methods Potential participants (n = 2131) were randomly selected from an IBD organisation's members' database; 605 volunteered and were posted three fatigue scales: Inflammatory Bowel Disease Fatigue scale, Multidimensional Fatigue Inventory and Multidimensional Assessment Fatigue scale and questionnaires assessing anxiety, depression, quality of life (QoL) and IBD activity. The questionnaires were tested for stability over time with another group (n = 70) of invited participants. Internal consistency was measured by Cronbach's alpha and test–retest reliability by the intraclass correlation coefficient (ICC). Results Four hundred and sixty‐five of 605 (77%) questionnaires were returned; of 70 invited, 48/70 returned test (68.6%) and 41/70 (58.6%) returned retest. The three scales are highly correlated (P < 0.001). Test–retest suggests reasonable agreement with ICC values between 0.65 and 0.84. Lower age, female gender, IBD diagnosis, anxiety, depression and QoL were associated with fatigue (P < 0.001) on univariable analysis. However, on multivariable analysis only depression and low QoL were consistently associated with fatigue, while female gender was associated on most scales. IBD diagnosis, age and other factors were not consistently associated with severity or impact of fatigue once other variables were controlled for. Conclusions All three fatigue scales are likely to measure IBD fatigue adequately. Responsiveness to change has not been tested. Depression, poorer QoL and probably female gender are the major associations of fatigue in IBD.